ANALISIS MANAJEMEN PROYEK PERANGKAT LUNAK SISTEM INFORMASI AKUNTANSI PADA BIRO SISTEM INFORMASI PT. X - Alusyanti Primawati; Dewi Mustari (Jurnal Sistem Informasi, 2013)
The software is an intermediary between system hardware computer with user as human. Based on the emerging software projects because of the importance of the functions already affects many functions in various aspects. Software projects that have become this need ultimately require management actions to manage the process in the project. Project management is necessary for the success of the project. Bereau Information System PT. X is one part of a company that provides software for functional PT. X. Analysis results from the concept of software project management information systems Bureau at PT. X when the process of designing application systems information accounting PT. X aims to answer how concept of project management Information Systems Bureau in designing the Accounting Information System applications. The methods used in this research is the study of the library with a general empirical approach based on experience and theories related to project management especially in software projects. The conclusions obtained that the activity of the management software on System Information Bureau is in compliance with the application of existing theory, but science is constantly evolving so as to do the development management activities after conducting evaluation regularly for the maintenance of long-term software project.